Biochar in cementitious material—A review on physical, chemical, mechanical, and durability properties - Pravina Kamini, G.; Kong, Fah Tee; Jolius, Gimbun; Chin, S. C. (AIMS Press, 2023)
Ordinary Portland Cement (OPC) is a crucial building component and a valuable strategic resource. The production of cement accounts for 5% to 10% of global carbon dioxide (CO2) emissions. Over the years, many researchers have been studying ways to reduce the amount of CO2 in the atmosphere caused by cement production. Due to its properties, biochar is found to be an interesting material to be utilised in the construction industry due to its effectiveness in CO2 sequestration. Biochar is a solid residue created by the thermal breakdown of biomass at moderate temperatures (350–700 ℃) without oxygen or with a small amount of oxygen, sometimes known as bio-carbon. Biochar has a wide range of uses, including those for heating and electricity generation, cleaning flue gases, metallurgy, animal husbandry, agriculture, construction materials, and even medicine. The objective of this paper is to review the potential of biochar as a cementitious material by evaluating its physical, chemical, mechanical, and durability properties. Using biochar as a cementitious material makes it possible to conclude that cement production will be reduced over time by partial replacement, which will also promote and encourage sustainable development in the future.